Analytical Evaluation of the Wing Box Splice Joint for Static & Fatigue Loading - R Sarath Kumar, G Krishnaveni, G Kavitha, E.S.Elumalai, D Dominic Xavier (International Journal of Advanced Science and Technology, 2019)
Aircraft is symbol of a high performance mechanical structure with high structural safety record. Safety and the structural weight are important parameters to be considered during the design phase. Analysis is carried out to find all of the theoretical stresses within and predict failure due to unknown stresses by showing stress concentrated areas in the material. Further, fatigue life to crack initiation can also be estimated by local stress strain approach. Based on the analysis the structural design, sizing and optimization is performed to meet the best feasible design. This ensures the safety of an aircraft keeping in account its structural weight. Analysis of the wing box is carried out for static and fatigue loading using finite element analysis